Abject Labours, Informal Markets: Revisiting the Law's (Re)Production Boundary - Kotiswaran, Prabha (feminists@law, 2014)
Over the past few decades, feminist legal scholars have successfully gendered several areas of legal doctrine, inlcuding labour law. In particular, they draw extensively on feminist theorizing of social reproduction to argue for the increased labour law protection of women's care work. While sympathetic to feminist efforts to redraw the 'production boundary', I critique in this article feminists' own reluctance to include within this production boundary the reproductive labour of women like sex workers, dancers and surrogates. I argue instead for the recognition of reproductive labour performed for the market as valuable, legitimate work. I then assess the implications of this redrawing of the 'reproduction boundary' for labour law. Through an examination of three generations of Indian labour law, I suggest that labour laws geared towards the informal economy best address female reproductive labourers' demands for both recognition and redistribution, but that for this, labour law itself needs to be reconceptualized, especially as the postcolonial state re-engineers labour laws in the prevalent economic climate to deliver benefits rather than workers' rights. A slightly modified version of this article will be published in the Employee Rights and Employment Policy Journal, vol 18, no 1 (2014).